The Need for Online Learning in Conditions Of Social Restrictions in Islamic Educational Institutions - Eddy Saputra; Rayung Wulan (CV ODIS, 2022)
Social restrictions do not mean stopping the learning process in Islamic Educational Institutions. The absence of physical contact changes the learning process, where learning must first be done in and outside the classroom. The learning pattern has changed over a long distance and must become a habit, even though it seems difficult at the initial stage. existing limitations must be used as opportunities to be able to develop learning media; one of the innovations carried out is online-based learning using applications that are widely available on digital platforms that are commonly used, especially among teenagers. Technology and networks are the dominant tools or media used in online learning amidst social restrictions. This research used a descriptive qualitative method, where the data were taken between observations and interviews. The purpose of this study is to provide input and information that limitations do not mean stopping creativity and innovation in implementing learning at Islamic Educational Institutions.